How important are local knowledge spillovers of public R&D and what drives them? - Leonie Koch; Martin Simmler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper analyzes the magnitude of local knowledge spillovers of public R&D in Germany and its determinants using patent application data. We identify three distinct transmission channels. First, firms file more patent applications when collaborating with (local) public institutions. Second, firms file more patent applications when citing a public patent. Third, local public R&D seems to increase the number of patent applications by local firms also via nonspecific knowledge spillovers. Using a fixed effect instrumental variable regression approach, we find evidence for substantial local spillovers and that these are driven by non-specific knowledge spillovers.
Keywords: I23; O34; O38; 330; R&D; university; research institutes; public spending